Inhibition of CDC25B With WG-391D Impedes the Tumorigenesis of Ovarian Cancer - Xiao, Yangjiong; Yu, Yang; Gao, Dan; Jin, Wangrui; Jiang, Pengcheng; Li, Yuhong; Wang, Chao; Song, Yuning; Zhan, Peng; Gu, Fei; Zhang, Cancan; Wang, Bin; et al. (Frontiers in Oncology, 2019)
Novel inhibitors are urgently needed for use as targeted therapies to improve the overall survival (OS) of patients with ovarian cancer. Here, we show that cell division cycle 25B (CDC25B) is over-expressed in ovarian tumors and associated with poor patient prognosis. All previously reported CDC25B inhibitors have been identified by their ability to reversibly inhibit the catalytic dephosphorylation activity of CDC25B in vitro; however, none of these compounds have entered clinical trials for ovarian cancer therapy. In this study, we synthesized a novel small molecule compound, WG-391D, that potently down-regulates CDC25B expression without affecting its catalytic dephosphorylation activity. The inhibition of CDC25B by WG-391D is irreversible, and WG-391D should therefore exhibit potent antitumor activity against ovarian cancer. WG-391D induces cell cycle progression arrest at the G2/M phase. Half maximal inhibitory concentration (IC50) values of WG-391D for inhibition of the proliferation and migration of eight representative ovarian cancer cell lines (SKOV3, ES2, OVCAR8, OVTOKO, A2780, IGROV1, HO8910PM, and MCAS) and five primary ovarian tumor cell lines (GFY004, GFY005, CZ001, CZ006, and CZ008) were lower than 10 and 1 μM, respectively. WG-391D inhibited tumor growth in nude mice inoculated with SKOV3 cells or a patient-derived xenograft (PDX). The underlying mechanisms were associated with the down-regulation of CDC25B and subsequent inactivation of cell division cycle 2 (CDC2) and the serine/threonine kinase, AKT. In conclusion, this study demonstrates that WG-391D exhibits strong antitumor activity against ovarian cancer and indicates that the down-regulation of CDC25B by inhibitors could provide a rationale for ovarian cancer therapy.